(untitled) (Research, Society and Development, 2020)
The quality of the sowing process is an indispensable factor to obtain productivity in the soybean culture, and this agricultural operation can be affected by several factors. The objective of this work was to evaluate the influence of the speed of the tractor-seeder set and the depth of fertilizer deposition on the quality of seed distribution and on the agronomic performance of the soybean crop. A completely randomized design was adopted in a 4 x 3 factorial scheme, with four years of sowing (5, 6, 7 and 8 km h-1) and three depths of fertilizer application in the furrow (9, 15 and 18 cm), with four repetitions per treatment. The variables analyzed were: sowing depth, number of days for emergence, longitudinal distribution of seedlings, initial and final stand, plant height, height of insertion of the first pod, number of pods per plant and productivity. The increase in the displacement speed of the tractor-seeder-fertilizer set increased the gap, reduced the acceptable gap and the initial stand. The application of fertilizer at a depth of 18 cm reduced the acceptable spacing, increasing the gap and seed depth. Plant height and first pod insertion, number of pods per plant and productivity were not affected by the speed of displacement and depths of fertilizer deposition. As the productivity components of the crop were not affected, aiming at higher operational yield and fuel economy, under the studied conditions, the sowing process in soybean can be carried out at the speed of 8 km h-1 and with the fertilizer applied at 9 cm depth.